EVALUASI IMPLEMENTASI PROGRAM INTERVENSI BERBASIS MASYARAKAT DI WILAYAH JAKARTA UTARA - Novianti Purnamasari; Tati Nuryati (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
The focus of this research is to evaluate how the implementation of IBM program activities and services by BNN Kota Jakarta Utara and Recovery Agency officers in the North Jakarta area. The indicator seen is how the conformity between the program being run with the expected results as a benchmark of the success of the program in the field. This study was conducted on 6 (six) villages in the North Jakarta area as villages that have criteria to conduct P4GN programs, the research was conducted in 2021. Qualitative research methods are used to determine the quality or quality of service from a product-based perspective, with a formative evaluation approach or program evaluation. The conclusions of this study are used for the submission of means in accordance with eligibility standards. Product evaluation activities include program operational goal setting activities, measurement criteria that have been achieved, comparing them between the field realities of goal formulation, and rational interpretation.